Maintenance of Mitochondrial Morphology in Cryptococcus neoformans Is Critical for Stress Resistance and Virulence - Andrew L. Chang (American Society for Microbiology, 2018)
ABSTRACT Mitochondria are essential organelles that act in pathways including ATP production, β-oxidation, and clearance of reactive oxygen species. They occur as a complex reticular network that constantly undergoes fusion and fission, mediated by dynamin-related proteins (DRPs). DRPs include Fzo1, which mediates fusion, and Dnm1, Mdv1, and Fis1, which mediate fission. Mitochondrial morphology has been implicated in virulence in multiple fungi, as with the association between virulence and increased mitochondrial fusion in Cryptococcus gattii. This relationship, however, has not been studied in Cryptococcus neoformans, a related opportunistic pathogen. C. neoformans is an environmental yeast that can adapt to the human host environment, overcome the innate immune system, and eventually disseminate and cause lethal meningoencephalitis. We used gene deletion of key DRPs to study their role in mitochondrial morphology and pathogenesis of this yeast. Interestingly, increasing mitochondrial fusion did not increase resistance to oxidative stress, unlike in model yeast. Blocking mitochondrial fusion, however, yielded increased susceptibility to oxidative and nitrosative stresses as well as complete avirulence. This lack of virulence was not mediated by any effects of altered mitochondrial function on two major virulence factors, capsule and melanin. Instead, it was due to decreased survival within macrophages, which in turn was a consequence of increased susceptibility to oxidative and nitrosative stress. Supporting this conclusion, reactive oxygen species (ROS) scavengers rescued the ability of fusion mutants to survive intracellularly. These findings increase our understanding of cryptococcal biology and virulence and shed light on an important group of proteins and cellular processes in this pathogen. IMPORTANCE C. neoformans is a yeast that causes fatal brain infection in close to 200,000 people worldwide every year, mainly afflicting individuals with AIDS or others who are severely immunocompromised. One feature of this microbe that helps it cause disease is that it is able to withstand toxic molecules it encounters when host cells engulf it in their efforts to control the infection. Mitochondria are important organelles responsible for energy production and other key cellular processes. They typically exist in a complex network that changes morphology by fusing and dividing; these alterations also influence mitochondrial function. Using genetic approaches, we found that changes in mitochondrial morphology dramatically influence cryptococcal virulence. We showed that this occurs because the altered mitochondria are less able to eliminate the harmful molecules that host cells produce to kill invading microbes. These findings are important because they elucidate fundamental biology and virulence and may suggest avenues for therapy.